Nodal induces apoptosis and inhibits proliferation in ovarian endometriosis-clear cell carcinoma lesions - Miura, Rinako (BMC Cancer, 2019)
BACKGROUND: Expression of Nodal, a member of the TGF-β superfamily, is commonly absent in differentiated tissues, while its re-expression occurs in a variety of human malignancy. However, little is known about its involvement in ovarian tumorigenesis. Herein, we focused on the functional roles of Nodal in ovarian endometriosis-carcinoma lesions. METHODS: Regulation and function of Nodal and its associated molecules, including Smad2, GSK-3β, and several cell kinetics-related molecules, were assessed using clinical samples consisting of 108 ovarian carcinomas and 33 endometriotic lesions, as well as ES-2 (ovarian clear cell carcinoma; OCCCa) and Ishikawa (endometrial carcinoma) cell lines. RESULTS: Nodal expression was significantly higher in endometriosis and OCCCa lesions as compared to that of non-OCCCas, with positive correlations to phosphorylated forms of both Smad2 (pSmad2) and GSK-3β. When compared to endometriotic lesions, the expression of Nodal and pSmad2 was significantly decreased in OCCCa. Treatment of Ishikawa cells with TGF-β1 resulted in transcriptional upregulation of Nodal, along with increased pSmad2 expression, while inhibition of GSK-3β also induced an increase in Nodal expression at the posttranslational level. Both ES-2 and Ishikawa cells stably overexpressing Nodal had increased susceptibility to apoptosis in response to treatment with cisplatin and doxorubicin, respectively, together with higher cleaved caspase-3 expression and decreased Bcl2/Bax ratio. Moreover, the stable Nodal-overexpressing cells showed reduced cell proliferation, along with increased expression of p27(kip1) and p21(waf1). In clinical samples, a significantly higher number of apoptotic cells and lower Ki-67 labeling indices were observed in Nodal-positive as compared to Nodal-negative OCCCa. CONCLUSIONS: These findings suggest that Nodal is a multifunctional cytokine involved in the modulation of cell kinetics in ovarian endometriosis-OCCCa lesions. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12885-019-5539-y) contains supplementary material, which is available to authorized users.